2022
DOI: 10.3389/fpubh.2022.870767
|View full text |Cite
|
Sign up to set email alerts
|

Role of Environmental Degradation, Institutional Quality, and Government Health Expenditures for Human Health: Evidence From Emerging Seven Countries

Abstract: The current study investigates the association of various economic, non-economic, governance, and environmental indicators on human health for seven emerging economies. Covering the period from 2000Q1 to 2018Q1, this study uses various panel data approaches for empirical estimations. The data is found first-order stationary. Besides, the panel slope is heterogeneous and cross-sectional dependence is present. Further, the cointegration association is found valid among the variables. Therefore, panel quantile re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 60 publications
2
22
0
Order By: Relevance
“…Specifically, this study observed the occurrence or outbreak of fatal diseases and their implications in disturbing various economic, educational, and government policies. In this regard, this study opted to examine the influence of various economic and noneconomic indicators on malarial incidence ( MI ) as this fatal disease not only adversely affects human health but also influences economic and educational activities ( 10 ). Concerning the primarily focused variables, this study considered two variables, including the education expenditures ( EDU ) and the technological innovation ( TI ), since the MI could have a substantial influence on disturbing economic, educational, and technological activities.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Specifically, this study observed the occurrence or outbreak of fatal diseases and their implications in disturbing various economic, educational, and government policies. In this regard, this study opted to examine the influence of various economic and noneconomic indicators on malarial incidence ( MI ) as this fatal disease not only adversely affects human health but also influences economic and educational activities ( 10 ). Concerning the primarily focused variables, this study considered two variables, including the education expenditures ( EDU ) and the technological innovation ( TI ), since the MI could have a substantial influence on disturbing economic, educational, and technological activities.…”
Section: Methodsmentioning
confidence: 99%
“…Omri et al ( 7 ) found that increasing health and R&D expenses aid in improving health outcomes. Wei et al ( 10 ) scrutinized the relationship between government health expenses, human capital, economic growth, and human health considering malarial incidents and cases in emerging economies. The empirical findings demonstrated that improvement in health expenditures helps in reducing health disasters such as malarial cases and incidents in emerging nations depicting negative and Granger causes of malaria cases in the country.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations